La aplicación de los valores en el fortalecimiento de la profesión en trabajo social en el cantón Machala - Chirimias Quinche, Kerly Karina (My University, 2021)
Ethical values are one of the most relevant points in the training of the Social Work professional, whose academic integration process must include an ethical culture and social responsibility as the main axis in their praxis, where it is allowed to act irreducibly in social interventions and studying the actions of the individual, contributing to the improvement of their social well-being in their relational spaces. Social Work has been immersed since its inception in the monitoring of norms, values and principles that allow it to be vehemently integrated into the work of the professional with the subject of law through their education, organization, planning, execution and evaluation with the full confidence in an ideal implementation of their work tools, however, it is important to emphasize that the Social Work Professional acts, through its Code of Professional Ethics and the Code of Ethics of the FITS and AIETS. Within the Ecuadorian scenario, the Social Worker acts under the premise of the National Objectives of Good Living and the Law of Professional Practice that governs the actions of the expert. From the intervention of Social Work and its capacity for the integration of skills and values, the promotion of human well-being is sought from its primary level, the family, to the macrosystem where the person develops around their culture, capable of identifying their rights based on the constitution and social premises. The values encompass all its systems, without utopias, only with an act based on ethical principles.
Los valores éticos, son unos de los puntos con mayor relevancia en la formación del profesional del Trabajo Social, cuyo proceso de integración académica debe incluir una cultura ética y de responsabilidad social como eje principal en su praxis, donde se permita actuar de forma irreductible en las intervenciones sociales y al estudiar el accionar del individuo, contribuyendo a la mejora de su bienestar social en sus espacios relacionales. El Trabajo Social se ha visto inmerso desde su comienzo en el seguimiento de normas, valores y principios que permiten integrarse con vehemencia en el quehacer del profesional con el sujeto de derecho a través de su educación, organización, planificación, ejecución y evaluación con la plena confianza en una implementación idónea de sus herramientas de trabajo, no obstante , es importante recalcar que el Profesional de Trabajo Social actúa ,mediante su Código de Ética Profesional y el código Deontológico de la FITS y AIETS . Dentro el escenario ecuatoriano el Trabajador Social actúa bajo la premisa de los Objetivos Nacionales del Buen Vivir y la Ley del Ejercicio Profesional que regenta el accionar del perito. Desde la intervención del Trabajo Social y su capacidad para la integración de habilidades y valores, se buscar la promoción del bienestar humano desde su nivel primario, la familia, hasta el macrosistema donde se desenvuelve la persona entorno a su cultura, capaces de identificar sus derechos basados en la constitución y premisas sociales. Los valores abarcan todos sus sistemas.
Keywords: VALOR ETICO; FORMACION PROFESIONAL; INTERVENCION; TRABAJO SOCIAL